A Study of Transfer Pricing, Leverage, Profitability, Sales Growth on Effective Tax Rate - Pangaribuan, Hisar; HB, Jouse Fernando; Agoes, Sukrisno; Sihombing, Jenny; Sunarsi, Denok (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
This study aims to find out whether transfer pricing, leverage, profitability, and sales growth can significantly affect the effective tax rate as a measure of tax avoidance practices. This research uses a descriptive method, revealing real facts based on secondary data collected from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange. The sample criteria in this study are the manufacturing companies that present complete financial statements, do not experience losses during the observation period, and have receivables from related parties. The number of companies that meet the criteria is 65 companies with three years of observation data, and the total sample of this research is 195 research data. The result of this study proposed that transfer pricing has no significant impact on tax avoidance, leverage has a significant effect on tax avoidance, profitability has a significant effect on tax avoidance, and sales growth has a significant effect on tax avoidance. The findings from this study are important inputs, especially for government tax recipients to pay more attention to the companies with a high profitability and sales growth, and when receivables shifts are more concentrated on receivables with related parties when compared to receivables from other parties, such companies tend to do tax efficiency through tax avoidance. Keywords : manufacturing company, tax avoidance, financial statement